Biosurfactant: an emerging tool for the petroleum industries - Sharma, Neha; Lavania, Meeta; Lal, Banwari (Frontiers in Microbiology, 2023)
The petroleum sector is essential to supplying the world's energy demand, but it also involves numerous environmental problems, such as soil pollution and oil spills. The review explores biosurfactants' potential as a new tool for the petroleum sector. Comparing biosurfactants to their chemical equivalents reveals several advantages. They are ecologically sustainable solutions since they are renewable, nontoxic, and biodegradable. Biosurfactants are used in a variety of ways in the petroleum sector. They can improve the mobilization and extraction of trapped hydrocarbons during oil recovery procedures. By encouraging the dispersion and solubilization of hydrocarbons, biosurfactants also assist in the cleanup of oil spills and polluted locations by accelerating their breakdown by local microorganisms. The review gives insights into alternative methods for the petroleum industry that are more viable and cost-effective.